DEVELOPING THE LEADERSHIP SCHOOL PRINCIPAL MODEL BASED OF KI HAJAR DEWANTARAâS LEADERSHIP TRILOGY - -, Tarto; Ekosiswoyo, Rasdi; Joko Raharjo, Tri; -, Masrukhi (The Journal of Educational Development, 2014)
School Principal leadership in its implementation in this study means: (1) describing and analyzing the values of leadership trilogy, (2) Principal leadership based on leadership Trilogy factually (3) the implementation of school principal leadership based on the leadership trilogy (4) the development of a principal leadership model based on the leadership trilogy. This study employs qualitative research approach using research and development design. The research follows these steps: (1) organizing, reducing and presenting the data, (2) classifying and analyzing data (3) the developing a leadership model based on leadership Trilogy. The research concludes that the implementation of school principal leadership based on leadership Trilogy include: (1) the implementation of school principal leadership based on leadership trilogy is still limited to the understanding on the perception of principals, (2) an effective leadership trilogy contains aspects of ing ngarsa sung tulada, ing Madya Mangun Karsa, and tut wuri handayani. The principal leadership model development based on Leadership Trilogy starts from a factual model, conceptual model design, hypothetical model design, and then final model. The strength of principal leadership based on Leadership trilogy is that it can be implemented in several leaderships: (1) authoritarian, (2) democratic, (3) permissive, (4) delegation, (5) family, (6) participatory, and (7) teling Seleng. The implementation of model is functional on: (1) authoritarian leadership of ing ngarsa sung tulada can be functional (2) participative leadership of ing Madya Mangun Karsa can be functional, and (3) the democratic leadership of tut wuri can handayani can be functional.